PENERAPAN METODE PEMBIASAAN DAN KETELADANAN DALAM MEMBENTUK IMAN DAN TAUHID SISIWA KELAS V DI SDIT IHYA AS-SUNNAH SINGKUT - bahresy, fiqqi assidieq; Syaiful Anam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The importance of shaping faith and tawhid from the primary school level is often not matched by students’ consistency in worship and their internalization of tawhid values, even in the context of Islamic integrated schools. This study aims to describe the implementation of habituation and role-modeling methods in building the faith and tawhid of fifth-grade students at SD IT Ihya As-Sunnah Singkut, as well as to identify supporting and inhibiting factors. This research employs a descriptive qualitative approach with Islamic education teachers, classroom teachers, and fifth-grade students as the main subjects, while data were collected through observations of religious activities, in-depth interviews, and documentation of school programs. The data were analyzed qualitatively through data reduction, data display, and conclusion drawing, and the validity of the findings was ensured through triangulation of techniques and sources.The results show that the habituation of worship (congregational prayer, dhuha prayer, Qur’an recitation, daily supplications) and the teachers’ role-modeling in religious attitudes and behavior are implemented in a structured manner and contribute positively to strengthening students’ faith and tawhid, as reflected in increased worship discipline, a sense of shame when violating religious rules, and an awareness of Allah’s constant supervision. However, the impact is not yet evenly distributed among all students due to differences in family background, peer environment, and the consistency of religious guidance outside school.The study recommends reinforcing collaboration among schools, teachers, and parents in continuing habituation and role-modeling at home so that the internalization of students’ faith and tawhid becomes more optimal